In Defense of Farmers’ and Community Rights: Justifying their Inclusion in Uganda’s Plant Variety Protection Legislation - Naluwairo, Ronald; Tabaro, Edgar (Advocates Coalition for Development and Environment ACODE, 2010)
In 2008, it was reported that President Museveni directed that issues of community rights (which in certain respects also include farmers’ rights) should be removed from the draft Plant Variety Protection Bill. There is no convincing reason that was given for the President’s directive. Apparently, in conformity with the President’s directive, when the draft Plant Variety Protection legislation was finally gazetted as a Bill, the substantive sections that had provided for the recognition and protection of farmers’ and community rights had been removed.